Diferentes técnicas de diagnóstico empregadas na estimativa de prevalência populacional de infecção por Cryptosporidium felis em gatos domiciliados no município de Araçatuba, São Paulo - Silveira Neto, Luiz da [UNESP] (2014)
The aim of this work was to compare the diagnostic methods by capture enzyme-linked immunosorbent assay (ELISA) and polymerase chain reaction (nested-PCR) to morphological analysis using the technique of flotation in water-ether followed by modified Kinyoun staining (microscopy) to estimate the shedding rate of Cryptosporidium spp. in stool samples of cats domiciled in urban area of municipality of Araçatuba, São Paulo State. Zoonotic potential of coccidian isolated in feces was investigated by molecular characterization. A total of 138 stool samples were collected random and proportionally from to cat population in each of the seven census areas belonging to the urban area. There was no disagreement between capture ELISA and microscopy (p = 1.0000) or between nested-PCR and microscopy (p = 0.1094); however, the degree of agreement varied from substantial (Kappa = 0.7948) to moderate (Kappa = 0.4647), respectively, in these diagnostic methods. Specificity of nested-PCR and ELISA capture were similar; however, the nested-PCR showed lower sensitivity, justified by the association between the intensity of the optical density and amplification of 18S rRNA subunit. We detected Cryptosporidium spp. in 9.4% of the samples by at least two diagnostic methods. With the 95% confidence, we estimate that shedding rate of Cryptosporidium oocysts ranged from 4.5% to 14.3% in the feline population of Araçatuba. All isolates sequenced showed 100% similarity with Cryptosporidium felis. We conclude that cats domiciled can contribute to environmental contamination of a municipality, although C. felis is not the primary etiologic agent of cryptosporidiosis in humans